2008
DOI: 10.4103/0971-5851.51442
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for gallbladder cancer : A population based case-control study in Delhi

Abstract: Background: Gallbladder (GB) cancer ranks among the first five common cancers in females in Delhi, India. The incidence rate of GB carcinoma is higher in North India compared to South India.Methods: A population based case-control study on 333 GB incident cases was carried out in Delhi to identify the risk factors. Cases were matched with two controls based on age (± 5 years), sex and marital status (in case of females)Results: Smoking and alcohol consumption increase the risk of GB cancer. The risk among thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 26 publications
1
32
2
Order By: Relevance
“…Here, cancer of gallbladder shows varying geographic distribution. In Delhi, it ranks among the first five common cancers in females (Tyagi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Here, cancer of gallbladder shows varying geographic distribution. In Delhi, it ranks among the first five common cancers in females (Tyagi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Lower socio-economic status is indirectly a result of illiteracy and poor education standards. This leads to unemployment and decreased livelihood capacity influencing preventive aspects of Gall bladder cancer [7].…”
Section: Socioeconomic Educational and Occupational Factorsmentioning
confidence: 99%
“…Some studies suggested an increased risk, while others suggested that long-term alcohol use might play a role by reducing the cholesterol saturation of bile. Recent data however point more in favour of the conclusion that Alcohol intake, smoking (cigarettes per day) and number of tobacco chewing per day are all independent risk factors for gall bladder carcinoma [7,12].…”
Section: Personal Habitsmentioning
confidence: 99%
“…Gallbladder cancer ranks among the first five common cancers in females in Delhi, India. 11 In the endemic zone of West Bihar and Eastern Utter Pradesh, it is the third most common malignancy of the alimentary tract. 12 It was found that increasing numbers of patients were being referred to our hospital in recent past, thus increasing the number of cases per year.…”
Section: Resultsmentioning
confidence: 99%